1997
DOI: 10.1093/brain/120.8.1301
|View full text |Cite
|
Sign up to set email alerts
|

Pallidotomy in Parkinson's disease increases supplementary motor area and prefrontal activation during performance of volitional movements an H2(15)O PET study

Abstract: Supplementary motor area and right dorsal prefrontal cortex activation in Parkinson's disease is selectively impaired during volitional limb movements. Since posteroventral pallidotomy improves motor performance in Parkinson's disease patients 'off' medication (i.e. off medication for 9-12 h), we hypothesized that it would also concomitantly increase supplementary motor area and dorsal prefrontal cortex activation. Six Parkinson's disease patients with a median total motor Unified Parkinson's Disease Rating Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
3
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(77 citation statements)
references
References 1 publication
9
63
3
2
Order By: Relevance
“…Indeed, greater activations of these regions were associated with [Piallat et al, 2008] and that SMA is clearly involved in internally generated motor actions [Debaere et al, 2003;Deiber et al, 1991;Jenkins et al, 2000;Ogawa et al, 2006;Rao et al, 1997]. SMA underactivity has been proposed to play an important role in the pathophysiology of PD motor symptoms [DeLong, 1990;Georgiou et al, 1993;Playford et al, 1992;Sabatini et al, 2000;Samuel et al, 1997]. Several imaging studies have shown how increased activation of SMA is often associated with motor improvement induced by effective treatments, such as GPi and STN surgery [Brooks and Samuel, 2000] as well as dopaminergic medications [Haslinger et al, 2001;Jenkins et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, greater activations of these regions were associated with [Piallat et al, 2008] and that SMA is clearly involved in internally generated motor actions [Debaere et al, 2003;Deiber et al, 1991;Jenkins et al, 2000;Ogawa et al, 2006;Rao et al, 1997]. SMA underactivity has been proposed to play an important role in the pathophysiology of PD motor symptoms [DeLong, 1990;Georgiou et al, 1993;Playford et al, 1992;Sabatini et al, 2000;Samuel et al, 1997]. Several imaging studies have shown how increased activation of SMA is often associated with motor improvement induced by effective treatments, such as GPi and STN surgery [Brooks and Samuel, 2000] as well as dopaminergic medications [Haslinger et al, 2001;Jenkins et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies have shown that PD leads to reduced regional cerebral blood flow (rCBF) and reduced blood oxygenation level dependent (BOLD) activation in the striatum, prefrontal cortex, and supplementary motor area (SMA) (Dirnberger et al, 2005;Grafton et al, 2006;Playford et al, 1992;Samuel et al, 1997;Yu et al, 2007). Two fMRI studies found that PD patients of moderate severity who had been treated with anti-parkinsonian medications for many years had increased BOLD activation compared to controls in the primary motor cortex (M1) when studied following a 12-h withdrawal from medication (Sabatini et al, 2000;Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in cerebral blood flow in the supplementary motor area has been correlated with the improvement of rigidity [13]. However, some investigations indicated that during motor execution, STN DBS induced an increased activation of the supplementary motor area [14,15,16]. The inconsistency might originate from the heterogeneity of patients enrolled in different studies.…”
Section: Discussionmentioning
confidence: 99%